Activation of AMPK sensitizes medulloblastoma to Vismodegib and overcomes Vismodegib‐resistance. Issue 6 (17th March 2021) - Gampala, Silpa; Zhang, GuangJun; Chang, Chun Ju; Yang, Jer‐Yen
Abstract: Vismodegib, a Smoothened antagonist, is clinically approved for treatment of human basal cell carcinoma (BCC), in the clinical trials of medulloblastoma (MB) and other cancers. However, a significant proportion of these tumors fail to respond to Vismodegib after a period of treatment. Here, we find that AMPK agonists, A769662, and Metformin, can inhibit GLI1 activity and synergize with Vismodegib to suppress MB cell growth in vitro and in vivo . Furthermore, combination of AMPK agonists with Vismodegib is effective in overcoming Vismodegib‐resistant MB. This is the first report demonstrating that combining AMPK agonist (Metformin) and SHH pathway inhibitor (Vismodegib) confers synergy for MB treatment and provides an effective chemotherapeutic regimen that can be used to overcome resistance to Vismodegib in SHH‐driven cancers.